Integration of the Paradigm of Religious Moderation in Islamic Pedagogy in the Digital Learning Ecology of Islamic Boarding Schools - Zidan; Riky Supratama (Al-Insan: Islamic and Humanities Perspectives Journal, 2025)
This study examines the integration of the religious moderation paradigm within Islamic pedagogy in the digital learning ecology of contemporary pesantren. The research is motivated by the growing tension between traditional value-based education and the rapid expansion of digital practices in pesantren, which has altered learning patterns, authority structures, and mechanisms of value transmission. Using a qualitative library research approach, this study analyzes primary and secondary literature related to religious moderation, Islamic pedagogy, digital pesantren transformation, and digital learning ecology. The analysis combines content analysis, comparative analysis, and conceptual synthesis to identify theoretical intersections and gaps. The findings reveal that although the values of religious moderation are inherently compatible with the principles of Islamic pedagogy, their implementation in digital spaces remains fragmented due to the lack of an integrative pedagogical framework. Digitalization offers both opportunities and risks for value internalization, demanding a renewed pedagogical model that aligns moderation values with digital learning dynamics. This study concludes that an integrative conceptual model is essential to strengthen value-based Islamic education in pesantren amid ongoing digital transformation.